PENERAPAN PERMAINAN OUTBOND BAGI ANAK USIA 4-5 TAHUN DI TK PERADABAN CILEGON- BANTEN - Ika Merdekawati; Fadlullah Fadlullah; Laily Rosidah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2019)
Outbound is an activity carried out in an open space emphasizing group dynamics through games so that children learn from the experiences they have done. This study aims to determine the application of outbound games for children aged 4-5 years in TK Civilization in Cilegon-Banten. This research use desciptive qualitative approach. The subjects of this study were children aged 4-5 years totaling 16 children. Data is collected through observation, field notes, interviews and documentation Data analysis uses data reduction. presentation of data and conclusions. Data validation is done by extension of observation, perseverance/regularity of observation, triangulation, member checking, negative case analysis, checking or discussion of colleagues and referential adequacy. The results of this study found that the application of outbound games to children aged 4-5 years in TK Cilegon Civilization well developed. This can be seen in the outbound game process, the process of implementing the outbound game goes well. The game goes through several stages, namely planning things that must be prepared such as preparing tools and materials needed to play outbound. The implementation of outbound activities such as how to play and the rules of play and reflection is the final stage of the game as an evaluation of the child's playing experience.